Role of bilateral internal iliac artery ligation in severe obstetric and gynaecological hemorrhage - Maheshwari, Shashi Lata Kabra; Kumari, Nisha; Ahmad, Syed N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Massive pelvic haemorrhage is a potentially lethal complication while undergoing obstetric and gynaecological surgery. The objective of this study was to study of role of bilateral internal iliac artery ligation in severe obstetric and gynaecological haemorrhage. It was a prospective interventional study carried out in a multi-speciality tertiary care hospital in New Delhi. Methods: Thirty-five patients (31 obstetric and 4 gynaecological) fulfilling the inclusion criteria over a period of 2 years were included in the study cohort after informed consent. After laparotomy, internal iliac arteries were exposed by incising the peritoneal fold between the infundibulo-pelvic and round ligaments. A number 1 silk suture and right-angled artery forceps were used to tie the internal iliac arteries approximately 1 inch below their origin. The success and complications of the procedure were analysed. Results: In the present study 31 out of 35 cases underwent BIIAL for obstetrical cause of haemorrhage and rest 4 for gynaecological cause. In 19 out of 31 patients, hysterectomy preceded or followed BILAL depending upon the clinical situation making a uterine salvation rate of 38.7%. The success rate of BIIAL was 67.7% in 31 obstetric cases. In the 4 gynaecological cases BILAL was done to arrest post-hysterectomy haemorrhage and success rate was 100%. Among 35 patients one patient died of haemorrhagic shock and 4 other died of full blown sepsis and MODS in surgical ICU. No significant procedure related complications were encountered. Conclusions: BILAL is a very effective procedure to control PPH and pelvic haemorrhage due to other causes and helps save the much precious lives and uteri. This procedure can always be tried where procedures like embolization are unavailable.